Synthesis and photophysical study of new blue fluorescent poly(azomethine-1, 3, 4-oxadiazole)s containing dimethylamino groups. (April 2018) - Hamciuc, Elena; Homocianu, Mihaela; Hamciuc, Corneliu; Carja, Ionela-Daniela
New aromatic polyazomethines were synthesized by polycondensation reaction of a diamine containing 1, 3, 4-oxadiazole ring, namely, 4, 4′-diamino-4″-[2-(4-phenoxy)-5-(4-dimethylaminophenyl)-1, 3, 4-oxadiazole)]triphenylmethane, with terephthalic aldehyde or bis(4-formylphenoxyphenyl)fluorene, by using N -methyl-2-pyrrolidinone (NMP) as solvent. The polymers were easily soluble in polar solvents, such as NMP, N, N -dimethylacetamide, or chloroform, and showed high thermal stability with the initial decomposition temperature above 415°C and the temperature of 10% weight loss in the range of 450–460°C. They exhibited high char yield at 800°C in the range of 52–56%. Optical properties were studied by absorption and photoluminescence spectra. In solution, the polymers presented two absorption maxima in the ranges 273–278 and 330–346 nm and emitted violet-blue light in the range of 413–468 nm, depending on the solvent polarity. The Stokes shift and emission quantum yield values depend on the polymer structure and solvent polarity. The emission intensity in NMP solution was enhanced upon increasing the HCl concentration, while the absorption spectral profile was slightly influenced.